12 Cases of Haglund’s Syndrome Detected through MRI - Zhou, Shuwei; Luo, Wuxing; Wang, Siyu; Zhang, Kun (Current Medical Imaging, 2023)
Background: Haglund’s syndrome is a common cause of heel pain but often neglected clinically. Haglund’s syndrome refers to a series of symptoms caused by impingement among posterosuperior prominence of the calcaneus, bursa and Achilles tendon. It is difficult to distinguish Haglund’s syndrome from other causes of heel pain by clinical diagnosis. Imageology is of great value in the diagnosis of Haglund’s syndrome. Objective: Our study aims to summarize the Magnet resonance (MR) imaging characteristics of Haglund’s syndrome and provide some reference to clinical work. Method: We retrospectively analyzed the MR images of 11 patients (6 males; 5 females; 6 right ankles, 4 left ankles, 1 bimalleolar ankles) who have been clinically and radiologically confirmed Haglund’s syndrome. Observation contents: morphological changes of calcaneus and talus, abnormal signal of calcaneus, abnormal Achilles tendon, and soft tissue abnormalities around Achilles tendon. Combined with literature reviews, summarize the MR imaging features of Haglund’s syndrome. Results: In 12 ankles, all ankles showed posterosuperior prominence of the calcaneus and Achilles tendon degeneration; 7 ankles showed bone marrow edema; 6 Achilles tendons were graded as either type II or type III tendinosis; 5 Achilles tendons showed partial tear; 12 ankles showed retrocalcaneal bursitis, 7 ankles showed retro-Achilles bursitis, 6 ankles showed Kager’s fat pad edema. Conclusion: This study found that MR images of Haglund's syndrome showed bone edema of the calcaneus, degeneration and partial tear of the Achilles tendon, the retrocalcaneal and retro-Achilles bursas, and Kager’s fat pad edema.
Keywords: Haglund’s deformity